Conditional Choice Modelling of Time Allocation Among Spouses in Transport Settings: Theory and Empirical Findings - Borgers, Aloys; Hofman, Frank; Timmermans, Harry (European Journal of Transport and Infrastructure Research, 2002)
As part of a wider rule-based model of activity behaviour, this paper explores the possibility to build a suite of linked conditional choice models to predict the amount of time spouses in a household spend on a set of activities together and alone. First, a choice model is used to predict the probability and hence the amount of time the spouses spend together and alone. Conditional on the outcome of this choice model, a second model predicts the amount of time that is spent by each spouse separately on a set of activities, as a function of sociodemographics, car availability and work status. The model is estimated using a small sample in Hendrik-Ido-Ambacht and Zwijndrecht in the Netherlands. The results indicate the model to have face validity. Rho-square values are also high.